ACTH-producing small cell neuroendocrine carcinoma from the gallbladder: a case report and literature review - Zhang, Xiaofang; Huang, Dihua; Pan, Xiaojie; Si, Qiya; You, Qiaoying (Frontiers in Endocrinology, 2023)
Ectopic adrenocorticotropic hormone syndrome (EAS) is a condition of hypercortisolism caused by non-pituitary tumors that secrete adrenocorticotropic hormone (ACTH). A rare occurrence of this syndrome is due to an ACTH-producing neuroendocrine tumor that originates from the gallbladder. One patient with severe hypokalemia and alkalosis was admitted to our hospital. Clinical presentations and radiographic findings confirmed the diagnosis of an aggressive ACTH-producing gallbladder malignancy with multiple liver metastases. The diagnosis was verified by pathological and immunohistochemical measurements from a biopsy of the hepatic metastasis. A literature review identified only four similar cases had been reported. Despite being rare and having a poor prognosis, hormone-producing neuroendocrine tumors that derive from the gallbladder should be considered in the differential diagnosis of ectopic ACTH syndrome.